Opinion Dynamics of Sznajd Model on Small-World Network (Communications in Computational Physics, 2009)
The society structure plays an important role in shaping the attitudes, beliefsand public opinion. For studying the role of the society structure in opinion dynamics,we analyze the Sznajd model on small-world network formed by adding shortcuts in alattice consisting of N nodes arranged in a ring and on two-dimensional (2-D) regularlattice. Through computer simulation, we find that there exists a pseudo-phase transition from the coexistence state for φφc, where φc issome threshold for the shortcut density φ, which is dependent of the complex networktopology and the dimensionality of complex networks. Our observations indicate thedependence of the opinion dynamics on the complex system topology.